Public perception towards the image and reputations of Universiti Teknologi MARA (UiTM) Bandaraya Melaka Campus / Nur Najmi Azmi...[et.al] - Azmi, Nur Najmi; Ibharim, Nur Fatihah; Nor Azizan, Nur Nablia Athirah; Jamree, Nur Syahirah; Abdul Aziz, Nurul Najihah (Faculty of Communication and Media Studies, 2016)
In this era, there are plenty ways to channel information or messages to the public . Public are the most important audience to an organization. Public also have their own role especially in the public relation industry. An addition, public and organization assist and help each other. As Public Relations practitioner, the purpose of public relations is to conducting, evaluating on a programmed, action and communication. This procedure is done to have the mutual understanding in an organization with the stakeholders. Other than that, this method and procedure also help the informants to achieve the public understanding that is necessary to an organization or institutions. Hence, this report examines the public perception towards Universiti Teknologi MARA (UiTM) Bandaraya Melaka Campus. The purpose of this study is to determine that the public perception towards the image and reputations of Universiti Teknologi MARA (UiTM) Bandaraya Melaka Campus. This research also conducted to fmd out how perceptions from public can affect UiTM images and how this organization handles the crisis and issues. The method of this research is qualitative which is In Depth Interview.